On locating-dominating number of comb product graphs - Aswan Anggun Pribadi; Suhadi Wido Saputro (Indonesian Combinatorial Society (InaCombS), 2020)
We consider a set D ⊆ V(G) which dominate G and for every two distinct vertices x, y ∈ V(G) D, the open neighborhood of x and y in D are different. The minimum cardinality of D is called the locating-dominating number of G. In this paper, we determine an exact value of the locating- dominating number of comb product graphs of any two connected graphs of order at least two.